Drug‐drug interactions with candidate medications used for COVID‐19 treatment: An overview - Haleh Rezaee; Fariba Pourkarim; Samira Pourtaghi‐Anvarian; Taher Entezari‐Maleki; Touraj Asvadi‐Kermani; Masoud Nouri‐Vaskeh (Wiley, 2021)
Abstract Drug‐drug interaction (DDI) is a common clinical problem that has occurred as a result of the concomitant use of multiple drugs. DDI may occur in patients under treatment with medications used for coronavirus disease 2019 (COVID‐19; i.e., chloroquine, lopinavir/ritonavir, ribavirin, tocilizumab, and remdesivir) and increase the risk of serious adverse reactions such as QT‐prolongation, retinopathy, increased risk of infection, and hepatotoxicity. This review focuses on summarizing DDIs for candidate medications used for COVID‐19 in order to minimize the adverse reactions.